To Study the Construction Techniques for Slum Rehabilitation In Metro Cites (Journal of Advances and Scholarly Researches in Allied Education, 2024)
With increasing urbanization, the need for adequate affordable shelter also increases. Housing shortage is one of the major challenges faced in developing countries like India. It is imperative to provide housing that caters to all income groups with special focus on the low and middle income groups. In order to provide low cost housing, it is essential to adopt innovative sustainable technologies which are affordable, fast track, cost effective, durable as well as environment friendly. This seminar  discusses emerging innovative technologies that can be adopted in the country to lower housing construction cost and help in provision of mass affordable housing. Some of the technologies discussed are Tunnel form, Sismo building technology, Light Gauge Steel Framed Structural technology, Precast Sandwich Panel technology etc. These technologies are reviewed on various parameters like local availability, affordability, energy efficiency, structural stability, quality, speed, cost effectiveness, eco friendliness and suitability for high rise construction. The advantages and limitations of the technologies are also mentioned. The seminar  highlights the potential barriers for adoption of these technologies in the Indian urban scenario and methods which can be employed to overcome those barriers in order to provide affordable housing for the low and middle income groups. Fast track construction is very much essential for the mass housing projects  like slum rehabilitation . For this rapid wall technique can be best option for construction